Routine preoperative colour Doppler duplex ultrasound scanning in anterolateral thigh flaps. Issue 8 (October 2016) - Lichte, Johanna; Teichmann, Jan; Loberg, Christina; Kloss-Brandstätter, Anita; Bartella, Alexander; Steiner, Timm; Modabber, Ali; Hölzle, Frank; Lethaus, Bernd
Abstract: The anterolateral thigh flap (ALT) is often used to reconstruct the head and neck and depends on one or more skin perforators, which often present with variable anatomy. The aim of this study was to localise and evaluate the precise position of these perforators preoperatively with colour Doppler duplex ultrasound scanning (US). We detected 74 perforators in 30 patients. The mean duration of examination with colour Doppler was 29 (range 13–51) minutes. Adequate perforators and their anatomical course could be detected preoperatively extremely accurately (p < 0.001). The mean difference between the preoperatively marked, and the real, positions was 6.3 (range 0–16) mm. There was a highly significant correlation between the accuracy of the prediction and the body mass index of the patient (0.75; p < 0.001). Neither the age nor the sex of the patient correlated with the accuracy of the prediction. Colour Doppler duplex US used preoperatively to localise perforators in ALT flaps is reliable and could be adopted as standard procedure.